Axis rotation MTD algorithm for weak target detection - Rao, Xuan; Tao, Haihong; Su, Jia; Guo, Xiaolu; Zhang, Jinze (Digital signal processing, 2014)
Weak targetʼs range migration often happens for long time integration in radar detection. To compensate for linear range migration and detect weak targets effectively, a novel coherent integration detection algorithm, axis rotation moving target detection (AR-MTD), is proposed. The AR-MTD eliminates the linear range migration by rotating two-dimensional echoes data plane, and realizes coherent integration via moving target detection (MTD). As the targetʼs resident time in a single range cell increases, the integration gain is improved clearly. Numerical experiments are presented to verify the reduction in the computational complexity of AR-MTD by selecting the velocity variation regions. Also, it is shown that the detection probability of AR-MTD is improved by nearly 20% when input signal-to-noise ratio (SNR) is −40 dB.